PATHOLOGICAL PHYSIOLOGY OF POSTHEMORRHAGIC ANEMIA - Rakhimova Gulnoz Shamsiyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. Blood loss is a compleх of pathological disorders and compensatory reactions directed against a decrease in the volume of circulating blood and hypoxia caused by a decrease in the respiratory function of the blood. Posthemorrhagic shock is a shock that occurs as a result of abundant acute blood loss. A decrease in the volume of circulating blood, a drop in blood pressure, a violation of microcirculation, disorders of the blood supply to vital organs (brain, heart, kidneys), the development of hypoxia, acidosis and intoxication, "vicious circles" in the pathogenesis leads to death. Post-hemorrhagic anemia-develops as a result of blood loss.